Predation by banana spiders (genus Cupiennius) on the treefrog Dendropsophus carnifex (Duellman, 1969) in Ecuador - Prémel, Vincent (2021)
We here report a case of predation involving Dendropsophus carnifex (Anura: Hylidae) and a banana spider.